Movement of prion‐like α‐synuclein along the gut–brain axis in Parkinson's disease: A potential target of curcumin treatment. (23rd June 2021) - Chetty, Devina; Abrahams, Shameemah; van Coller, Riaan; Carr, Jonathan; Kenyon, Colin; Bardien, Soraya
Abstract: A pathological hallmark of the neurodegenerative disorder, Parkinson's disease (PD), is aggregation of toxic forms of the presynaptic protein, α‐synuclein in structures known as Lewy bodies. α‐Synuclein pathology is found in both the brain and gastrointestinal tracts of affected individuals, possibly due to the movement of this protein along the vagus nerve that connects the brain to the gut. In this review, we discuss current insights into the spread of α‐synuclein pathology along the gut–brain axis, which could be targeted for therapeutic interventions. The prion‐like propagation of α‐synuclein, and the clinical manifestations of gastrointestinal dysfunction in individuals living with PD, are discussed. There is currently insufficient evidence that surgical alteration of the vagus nerve, or removal of gut‐associated lymphoid tissues, such as the appendix and tonsils, are protective against PD. Furthermore, we propose curcumin as a potential candidate to prevent the spread of α‐synuclein pathology in the body by curcumin binding to α‐synuclein's non‐amyloid β‐component (NAC) domain. Curcumin is an active component of the food spice turmeric and is known for its antioxidant, anti‐inflammatory, and potentially neuroprotective properties. We hypothesize that once α‐synuclein is bound to curcumin, both molecules are subsequently excreted from the body. Therefore, dietary supplementation with curcumin over one's lifetime has potential as a novel approach to complement existing PD treatment and/or prevention strategies. Future studies are required to validate this hypothesis, but if successful, this could represent a significant step towards improved nutrient‐based therapeutic interventions and preventative strategies for this debilitating and currently incurable disorder. Abstract : Alpha‐synuclein aggregation in Parkinson's disease (PD) first occurs in the gut, brain, or in between, with prion‐like, bidirectional flow of synuclein pathology along the gut–brain axis. Appendix, tonsil, and vagus nerve surgeries seem ineffective in preventing PD. We propose that curcumin binds to α‐synuclein and both molecules are excreted, preventing toxic protein aggregates from moving to the brain and causing PD. Thus, dietary consumption of curcumin has potential as a novel PD therapy.